As relações entre as forças armadas e a sociedade uruguaia no governo de Tabaré Vásquez - Coelho, Pablo Martins Bernardi [UNESP] (2013)
In this work we analyze the relationship between the military and society during the Uruguayan government Tabaré Vázquez, initiated in March 2005. We postulate that this government has set up a critical juncture in the history of civil-military relations in Uruguay. This was started because a broad investigative process relating to acts performed by the military dictatorship period (1973-1985) and for which has not yet been found no solution. In this framework, lies the research process he undertook the government of President Tabaré Vázquez on the fate of imprisoned and missing during the dictatorship and, particularly, the first findings of human remains in clandestine graves located in military units, since the end of 2005. If this is confirmed, his legacy will present significant changes in the model of military subordination that began to be established in Uruguay in the early twentieth century and was perpetuated, only stopping dictatorial period, over 100 years